2017
DOI: 10.4073/csr.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

12‐step programs for reducing illicit drug use

Abstract: This Campbell systematic review examines the effectiveness of 12‐step programs in reducing the use of illicit drugs. The review summarises findings from 10 studies, nine of which were conducted in the United States. The main evidence presented in this review suggests that 12‐step programs for reducing illicit drug use are neither better nor worse than other interventions. This conclusion should be read with caution given the weakness of the evidence from the studies. The power to detect a difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 79 publications
(349 reference statements)
0
14
0
Order By: Relevance
“…However, the searches revealed the existence of high‐quality systematic reviews of 12‐step versus TAU (Bøg et. al., ; Ferri et al, ) and no further RCTs of this comparison. Therefore, we re‐focused the current review to compare DBT to either TAU or 12‐step programmes.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…However, the searches revealed the existence of high‐quality systematic reviews of 12‐step versus TAU (Bøg et. al., ; Ferri et al, ) and no further RCTs of this comparison. Therefore, we re‐focused the current review to compare DBT to either TAU or 12‐step programmes.…”
Section: Methodsmentioning
confidence: 87%
“…Contextual evidence from observational studies not included in this review suggested that several demonstrate that longer duration of AA attendance is associated with less drinking than shorter attendance (Grossop et al, ; Laudet et al, ; Moos & Moos ). Two uncontrolled studies (Moos & Moos, ; Timko, Moos, Finney, & Lesar, ), not included in previous systematic reviews (Bøg et al, ; Ferri et al, ; Nielsen et al, ), found an overall relationship (positive effect) between 12‐step self‐help group participation–attendance and positive drinking outcomes. Such outcomes are consistent with conclusions from previous systematic reviews of the effects of 12‐step programmes for SUD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations